2013
DOI: 10.1111/aor.12126
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of the Delivery of Gaseous Microemboli and Hemodynamic Energy for a Diagonal and a Roller Pump During Simulated Infantile Cardiopulmonary Bypass Procedures

Abstract: Cardiopulmonary bypass (CPB) is used for a variety of procedures in pediatric patients. Flow settings of the CPB pump have dramatic effects on patient outcome, and gaseous microemboli delivery within the CPB circuit has been linked to neurological complications. To ensure the ongoing improvement of pediatric CPB, consistent evaluation and improvement of the equipment is necessary. In this study we analyze the Jostra HL-20 roller pump (Jostra USA, Austin, TX, USA) and a Medos Deltastream DP3 diagonal pump (MEDO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…We also found the number of GME to be increased in hypothermic conditions due to increased blood viscosity. Therefore, flow rate, blood temperature and perfusion mode have great effects on GME transmission during CPB procedure, confirming our previous findings [13-15,22-25] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found the number of GME to be increased in hypothermic conditions due to increased blood viscosity. Therefore, flow rate, blood temperature and perfusion mode have great effects on GME transmission during CPB procedure, confirming our previous findings [13-15,22-25] .…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that keeping the arterial purge line open can further reduce the total volume and size of microemboli delivered to the patient [22-25] . However, keeping the purge line open also shunts a significant amount of blood away from the patient and puts the patient at risk for hypoperfusion and a decreased post-arterial filter THE, especially at lower flow rates [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, total GME counts <40 µm were approximately 100% higher in the postoxygenator site compared to the preoxygenator site (Table , CP groups in A, B, and C). Our results confirm that centrifugal pumps break the GME into smaller‐sized air particles compared to those of the roller pumps . We also observed a dramatic decrease in GME volume and count in all experimental circuits with BB, reinforcing the finding that the BB is an effective means for capturing GME.…”
Section: Discussionsupporting
confidence: 84%
“…Ranjodh Dhami et al. of the Penn State Hershey Children's Hospital, Hershey, PA, USA, studied in vitro the delivery of gaseous microemboli and hemodynamic energy for a diagonal and a roller pump during simulated infantile CPB procedures. At most flow settings, the diagonal pump delivered fewer microemboli than the roller pump at the preoxygenator site, with an exception at 1200 mL/min under pulsatile mode.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%